A comparative study of Afrikaner Economic Empowerment and Black Economic Empowerment : a case study of a former South African parastatal in Vanderbijlpark - Xaba, Nkhaba Jantjie (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.